A bibliometric analysis of the global trend of using alginate, gelatine, and hydroxyapatite for bone tissue regeneration applications - Hussin M.S.F.; Serah A.M.; Azlan K.A.; Abdullah H.Z.; Idris M.I.; Ghazali I.; Shariff A.H.M.; Huda N.; Zakaria A.A. (MDPI AG, 2023)
Alginate; Clinical research; Data mining; Engineering research; Hydroxyapatite; Scaffolds (biology); Tissue; Bibliometric analysis; Bone tissue engineering; Bone tissue regeneration; Bone tissue scaffolds; Chinese Academy of Sciences; Clinical outcome; Knowledge Visualization; Materials science and engineering; Biomedical materials